Case report: Withdrawal of angiotensin-converting enzyme inhibitors in children with advanced chronic kidney disease and rapidly declining kidney function - Seeman, Tomáš; Dušek, Jiří (Frontiers in Pediatrics, 2023)
Background: It is not known whether withdrawal of angiotensin-converting enzyme inhibitors (ACEI) in children with advanced chronic kidney disease (CKD) is beneficial similar to adults. We report a case series of children with CKD whom ACEIs was stopped. Methods: In the last five years, we stopped ACEIs in all seven consecutive children on ACEI therapy with rapidly declining CKD stage 4-5. The median age was 12.5 years (range 6.8–17.6); the median estimated glomerular filtration rater (eGFR) at stopping ACEIs was 12.5 ml/min/1.73m2 (range 8.8–19.9). Results: Six to twelve months after stopping ACEI the eGFR increased in five children (71 %). The median absolute increase of eGFR was 5.0 ml/min/1.73m2 (range –2.3 to +20.0) and relative increase of eGFR was 30 % (range -34 to +99). The median follow-up after stopping ACEIs was 2.7 (range 0.5 – 5.0) years, either until the start of dialysis (n=5) or until the last follow-up without dialysis (n=2). Conclusions: This case series showed that withdrawal of ACEIs in children with CKD stage 4-5 and rapidly declining kidney function may lead to an increase in eGFR.